(untitled) - Connolly, Thomas M. (Boston, 2010)
This best-selling text introduces the theory behind databases in a concise yet comprehensive manner, providing database design methodology that can be used by both technical and non-technical readers. The methodology for relational Database Management Systems is presented in simple, step-by-step instructions in conjunction with a realistic worked example using three explicit phases—conceptual, logical, and physical database design.
Cơ sở dữ liệu nâng cao
Keywords: Database design,Thiết kế cơ sở dữ liệu